2012
DOI: 10.2215/cjn.04820511
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of IgA Nephropathy with Nephrotic Syndrome

Abstract: Summary Background and objectives Nephrotic syndrome (NS) is a rare manifestation of IgA nephropathy (IgAN). Clinical characteristics and long-term outcomes of this condition have not yet been explored. Design, setting, participants, & measurements A multicenter observational study was conducted between January 2000 and September 2010 in 1076 patients with biopsy-proven IgAN from four medical centers in Korea. The primary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
95
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 26 publications
7
95
1
Order By: Relevance
“…Kim et al (33) concluded that IgAN patients with NS have a worse prognosis, but it is notable that many of the patients had significant proliferative lesions. In fact, only four patients had the exclusively mesangial proliferative disease and diffuse podocyte foot process effacement that was characteristic of patients in our cohort (33). In the series reported herein, all 17 patients showed a response to corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 63%
“…Kim et al (33) concluded that IgAN patients with NS have a worse prognosis, but it is notable that many of the patients had significant proliferative lesions. In fact, only four patients had the exclusively mesangial proliferative disease and diffuse podocyte foot process effacement that was characteristic of patients in our cohort (33). In the series reported herein, all 17 patients showed a response to corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 63%
“…Previously, the best single predictor for renal deterioration was severe proteinuria on urine dipstick testing (C100 mg/dL), followed by hypoalbuminemia, mild hematuria, serum total protein levels, diastolic blood pressure, and histological grade, in a cohort study with 10 years follow-up from 1995 in Japan, the cohort of which exhibited a younger median age (27.7 years) and a peak distribution of age ranges in the teens [11,12]. A recent report suggested that IgAN with nephrotic syndrome had a worse renal outcome compared to IgAN with non-nephrotic syndrome unless partial or complete remission was achieved [13]. Further studies are necessary to elucidate the risk factors or predictors for renal deterioration in IgAN in the present era utilizing the J-RBR, possibly as part of a new secondary clinical study.…”
Section: Discussion and Commentsmentioning
confidence: 99%
“…Immunoglobulin A nephropathy (IgAN), the most common form of glomerulonephritis, is characterized by the accumulation of IgA immune complex deposits in the mesangium of the kidney [1]. The Oxford classification of IgAN has been widely adopted since 2009, which includes several definitive histological features: mesangial hypercellularity (M), endocapillary proliferation (E), segmental sclerosis or adhesion (S) and tubular atrophy/interstitial fibrosis (T) [2].…”
Section: Introductionmentioning
confidence: 99%